STRATEGY FOR OPTIMIZING THE COSTS OF HOTEL BUSINESS ENTERPRISES IN TIMES OF WAR - Zavidna, Liudmyla (Social Development: Economic and Legal Issues, 2025)
The full-scale war has posed an unprecedented challenge for entities within Ukraine’s hotel industry. Amid a sharp contraction in consumer demand, a decline in innovation activity, and intensifying competitive pressure, enterprises in the sector confront numerous significant challenges, among which the imperative of rational and effective cost management stands out as particularly critical. Costs incurred by hotel business enterprises constitute a vital economic indicator that defines the level of financial stability, underpins revenue forecasting, and reflects the efficiency of revenue management systems. The primary objective of this research is to develop and implement a strategy for optimizing costs in hotel business enterprises under wartime conditions. The study employs general scientific methodologies, including both quantitative and qualitative analyses, alongside specialized economic techniques such as comparison, generalization, and a systematic approach. To evaluate enterprise performance in the hotel services market, official data from the State Statistics Service of Ukraine, surveys of hotel business owners and managers, and an extensive review of scholarly literature were utilized. Monitoring the cost structure of hotel enterprises represents a critical phase in identifying avenues for cost optimization, as the results obtained provide not only a means for financial monitoring but also enable the identification of potential opportunities for the optimization of costs and resources aimed at enhancing operational efficiency. To ensure the objectivity, consistency, and reproducibility of the research findings, a portfolio of universal cost optimization principles was formulated based on the United States Industry Accounting Library (USALI) recommendations. These principles function as foundational guidelines, establishing essential benchmarks for decision-making in cost management. The cost management methods identified exhibit significant applied value, justifying the necessity for further investigation into priority approaches to their optimization. By identifying the causes of inefficient utilization of resource potential, a cost dissipation profile for hotel business enterprises was developed using the investigated methods. This profile facilitates the forecasting of financial fluctuations and serves to mitigate and minimize adverse financial outcomes amid unfavorable demand trends. Moreover, it enables the strategic redistribution of resources to effectively meet consumer demand during cyclical, seasonal, trend-driven, and stochastic fluctuations.